2014
DOI: 10.1590/s1516-89132014005000018
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of C-phycocyanin from Arthronema africanum (Cyanophyceae)

Abstract: Pure C-phycocyanin (C-PC) was isolated from Arthronema africanum to evaluate its potential antitumor effects in vivo and in vitro. Experimental myeloid Graffi tumor in hamsters was used as a model. The cell proliferation assayshowed that C-PC treatment, at concentration of 100 µg mL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 36 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Phycocyanin also scavenges free radicals from damaged nerve cells, which could avoid DNA oxidative damage cause from free radicals and prevent neuronal cell apoptosis 60 , 61 . There are more and more researches have shown that phycocyanin plays an effective anti-cancer role in various cancer cell types (such as breast cancer 57 , 62 , liver cancer 63 , lung cancer 64 , 65 , colon cancer 66 , Leukemia 67 and bone marrow cancer 68 and so on) in vitro and in vivo . Morcos first discovered the laser-induced cytotoxicity of phycocyanin, which could kill tumor cells, while the damage to normal tissue is minimal 69 .…”
Section: Phycocyanin: General Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Phycocyanin also scavenges free radicals from damaged nerve cells, which could avoid DNA oxidative damage cause from free radicals and prevent neuronal cell apoptosis 60 , 61 . There are more and more researches have shown that phycocyanin plays an effective anti-cancer role in various cancer cell types (such as breast cancer 57 , 62 , liver cancer 63 , lung cancer 64 , 65 , colon cancer 66 , Leukemia 67 and bone marrow cancer 68 and so on) in vitro and in vivo . Morcos first discovered the laser-induced cytotoxicity of phycocyanin, which could kill tumor cells, while the damage to normal tissue is minimal 69 .…”
Section: Phycocyanin: General Propertiesmentioning
confidence: 99%
“…Among them, phycocyanin, a marine drug, plays an anti-proliferation and pro-apoptotic effects on different cancer cell lines in vitro, while phycocyanin have no side effects on normal tissue cells 84 , 85 . More and more evidences have proved that phycocyanin has an effective anti-cancer effect on various cancer cell types (such as breast cancer 57 , 62 , liver cancer 63 , lung cancer 64 , 65 , colon cancer 66 , Leukemia 67 and bone marrow cancer 68 ) in vitro and in vivo . High-dose phycocyanin does not induce significant toxic symptoms or mortality in animal experiments 81 , 86 .…”
Section: Phycocyanin and Cancermentioning
confidence: 99%
“…Accumulating evidence shows that phycocyanin has a potent anticancer effect both in vitro and in vivo on a variety of cancer cell types, such as lung cancer 7 , colon cancer 8 , breast cancer 9 and bone marrow cancer 10 . In addition, administration of phycocyanin at the high doses from 0.25 to 5.0 g/kg body weight (w/w) does not induce noticeable symptoms of toxicity nor mortality in animals 11 .…”
mentioning
confidence: 99%
“…Previous assessment of the anti-tumour activity of C-PC have been focused on the C-PC isolated mainly from Spirulina platensis [5], in addition to other rich sources including Arthronema africanum [43], Limnothrix sp. [44,45], Porphyra yezoensis [46], and Porphyra haitanensis [47].…”
Section: Discussionmentioning
confidence: 99%